THE CONTROL OF HEPATITIS B VIRUS INFECTION WITH VACCINE IN YUPIK ESKIMOS: DEMONSTRATION OF SAFETY, IMMUNOGENICITY, AND EFFICACY UNDER FIELD CONDITIONS - HEYWARD, WILLIAM L.; BENDER, THOMAS R.; MCMAHON, BRIAN J.; HALL, DAVID B.; FRANCIS, DONALD P.; LANIER, ANNE P.; ALWARD, WALLACE L. M.; AHTONE, JERAL L.; MURPHY, BERT L.; MAYNARD, JAMES E. (Oxford University Press, 1985)
In 1981, a hepatitis B vaccine demonstration project was initiated among Yupik Eskimos of southwest Alaska to demonstrate that, under field conditions, the vaccine was safe, immunogenic, and efficacious. Laboratory tests for serologic markers of hepatitis B virus infection (HBsAg, anti-HBs, and anti-HBc) performed on sore collected in May 1981 from 3,988 residents of 17 remote Eskimo villages revealed that 2,645 (66.3%) had no evidence of hepatitis B virus infection. Because of a limited supply of vaccine, specific criteria for selection were used so that those at highest risk of infection would be immunized first. In November 1981, the first dose of vaccine was administered to 1,693 carefully selected individuals. The second dose was administered to 1,678 (99.1%) of those who received the first dose, and the final dose was administered to 1,630 persons (96.3%). Serologic follow-up showed the vaccine to be safe (0.4%) experienced minor adverse reactions) and immunogenIc (97.4% developed antibody). Vac cine-Induced antibody levels were significantly higher for persons loss than 30 years of age ( p < 0.001) and for females ( p < 0.001). Vaccine recipients were also protected from hepatitis B virus infection ( p = 0.002). This public health measure proved to be feasible and effective in this remote arctic population despite difficult conditions for delivery and administration of this temperature-sensitive vaccine. This strategy for immunization is now being applied on a larger scale in Alaska as part of a program for the primary prevention of this infection and its sequelae.